HUBUNGAN DIET RENDAH GARAM DAN KEPATUHAN MINUM OBAT DENGAN PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI RAWAT JALAN DI POLI PENYAKIT DALAM - jukarnain; Nelly Nugrawati (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2022)
Objective: The purpose of this study was to determine the relationship between a low-salt diet and medication adherence with a decrease in blood pressure in outpatient hypertension patients at Bhayangkara Hospital Makassar. Methods: used in this study was quantitative with a population cross sectional approach and the samples in this study were all outpatients at the internal medicine clinic at Bhayangkara Hospital Makassar in September-October 2018. Results: The results showed that there was a relationship between low salt diet and decrease in blood pressure in patients with hypertension (0.001), there is a relationship between adherence to medication and a decrease in blood pressure in patients with hypertension (0.003). Conclusion: There is a relationship between a low salt diet and medication adherence with a decrease in blood pressure in patients with hypertension. Suggestion: for further researchers, it is hoped that through this research they can obtain information that can support further research and are expected to be able to raise new things related to hypertension that have not been raised in this study